PERAN INFRASTRUKTUR TRANSPORTASI TERHADAP PRODUKTIVITAS TENAGA KERJA INDUSTRI MANUFAKTUR DI INDONESIA - Pratama, Dedi; Khoirunurrofik , Khoirunurrofik (Jurnal Ekonomi dan Pembangunan, 2023)
Research on the role of transportation infrastructure (roads, ports, and airports) on regional development is generally still at the macro level (national and regional). This study discusses the impact of transportation infrastructure on regional development at the micro level, specifically on the labor productivity of the manufacturing industries. Using Indonesian manufacturing industries data in 2017, this study shows the positive influence of road and port transportation infrastructure on labor productivity in the manufacturing industries. The airport transportation infrastructure has no significant effect on the labor productivity of the manufacturing industries. This study also shows differences in the impact of transportation infrastructure on companies located on Java Island with companies located outside Java Island, as well as companies categorized as a large industry and companies categorized as middle industry.